Seizures Following DTP Immunization - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1988)
The incidence of seizures following the administration of DTP vaccine at the Group Health Cooperative of Puget Sound, Seattle, has been estimated by epidemiologists at the Harvard School of Public Health, Boston, and by the Boston Collaborative Drug Surveillance Program, Waltham, Mass.